PRAKTEK JUAL BELI BUAH DURIAN SISTEM TEBAS DALAM PERSPEKTIF HUKUM ISLAM DI DESA SONGGON KABUPATEN BANYUWANGI - Nasrullah, M. Alaika; Faizi, Fikri Fahmi (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
The purpose of this study was to determine the practice of buying and selling durian fruit with a slashing system. In addition, to find out how the views of Islamic law on the practice of buying and selling durian fruit with this slashing system. This type of research is qualitative research. The results showed that the practice of buying and selling durian fruit with a slashing system in Songgon Village, Banyuwangi Regency, in practice there are elements that can benefit and harm one party between the seller and the buyer. In practice there is also an element of gharor which is still not clear whether the durian fruit can be harvested or even exposed to pests or fall before harvest time. Because buyers still have to wait two months more to be able to harvest durian fruit. In the practice of buying and selling durian fruit is not in line with the wishes of syara', where in practice it is selling unripe fruit or selling fruit that is still on the tree, so that there is an element of uncertainty (gharar) in this transaction.